THE FEATURES OF TEACHER TRAINING FOR MEDIA EDUCATION OF STUDENTS IN THE DEVELOPED ENGLISH-SPEAKING COUNTRIES - Наталія Приходькіна (National Academy of Educational Sciences of Ukraine, 2021)
Media literacy deserves a special place in teacher education, as it stimulates critical thinking, including a variety of reading, writing and speaking skills, the use of computer technology and the decoding of various types of information. In the article, the author analyzes the features of teacher training for media education of students in developed English-speaking countries. Media literacy, introduced into training programs, can be very useful and effective. Preparation for the development of media literacy of teachers can be carried out in the process of advanced training, educational psychology courses, basic training courses and teaching practice. Media literacy contributes to critical thinking, focusing on social issues, understanding the branches of knowledge and children, and shaping teacher professionalism. Media literacy offers prospective teachers new opportunities to succeed and improve school performance. The Canadian, British, Australian, American colleges and universities train teachers in media education. They are acquainted with the media education theory and practice, modern technologies of media education on the system of «key concepts», possibilities of using digital technologies in the process of media education of students. The National Media Education Associations offer vocational courses and media workshops for teachers. One of the most popular ways to improve the qualification and self-education of teachers is MOOC (Futurelearn, Coursera, EdX).